2012
DOI: 10.1016/j.str.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Discoidin Domain Receptor 1 Extracellular Region Bound to an Inhibitory Fab Fragment Reveals Features Important for Signaling

Abstract: SummaryThe discoidin domain receptors, DDR1 and DDR2, are constitutively dimeric receptor tyrosine kinases that are activated by triple-helical collagen. Aberrant DDR signaling contributes to several human pathologies, including many cancers. We have generated monoclonal antibodies (mAbs) that inhibit DDR1 signaling without interfering with collagen binding. The crystal structure of the monomeric DDR1 extracellular region bound to the Fab fragment of mAb 3E3 reveals that the collagen-binding discoidin (DS) dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
133
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(139 citation statements)
references
References 44 publications
4
133
0
1
Order By: Relevance
“…This is supported by the results of an X-ray crystallographic study, which suggested that asparagine 211 of DDR1 is one of the residues that interacts with calcium in one of the two proposed calcium-binding sites in the discoidin-like domain. 5) In addition, we observed that depletion of calcium impaired the generation of high-molecular-mass forms of DDR1 and DDR2, similarly to the effect of mutations in asparagines 211 and 213 of DDR1 and DDR2 respectively (Wong et al, unpublished results).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This is supported by the results of an X-ray crystallographic study, which suggested that asparagine 211 of DDR1 is one of the residues that interacts with calcium in one of the two proposed calcium-binding sites in the discoidin-like domain. 5) In addition, we observed that depletion of calcium impaired the generation of high-molecular-mass forms of DDR1 and DDR2, similarly to the effect of mutations in asparagines 211 and 213 of DDR1 and DDR2 respectively (Wong et al, unpublished results).…”
Section: Discussionmentioning
confidence: 73%
“…In fact, an X-ray crystallographic study of DDR1 found that asparagine 211 is one of two sites occupied by N-glycan. 5) In addition, our in silico analysis predicted asparagine 213 of DDR2 and asparagine 211 of DDR1 as the sites of highest Nglycosylation potential among the sites in them (Supplemental Table S3). Another possibility is that this site and/or its N-glycan is associated with the binding of calcium in the discoidin-like domain, and that complex formation with calcium is required for the proper posttranslational maturation of DDRs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…17,18) In addition, an X-ray crystallographic study has characterized another structural unit in DDR proteins, called a DS-like domain, which was named owing to a structural similarity to the DS domain. 19) It was suggested that this domain forms a specific contact with the DS domain and is necessary for the activation of the receptors. This study also demonstrated that the DS-like domain contains a calcium-binding site and two N-glycosylation sites.…”
mentioning
confidence: 99%